Desonestidade acadêmica nos programas de pós-graduação stricto sensu em Ciências Contábeis - Fróes, Regina Cardoso (2020)
The main aim of this research was to analyze the students’ and professors’ perceptions about the dishonest academic behaviors in the Accounting Sciences post graduation strictu sensu courses. To achieve this aim, two questionnaires which were adapted from the studies by Braun e Stallworth (2009) and Oliveira Neto and Chacarolli Júnior (2013) were applied to 86 students and 48 professors who accepted to take part in the research. Non-parametric tests were used, such as the Mann-Whitney test, to analyze the two samples in order to compare the averages between the two groups, and the Wilcoxon test for the paired samples to compare the opinion of the participants regarding the perception of the opinion of the other group. The research used the dishonest behavioral analyzes proposed by Pavela (1978; 1997): fraud, cheating and use of materials without the authors’ authorization, making up information, references or study results; plagiarism and help from other students in the academic dishonesty practices complemented with a category reported by Diniz (2015; 2018) and Frezatti (2018): auto-plagiarism and similarities in the research. It was identified that the students and the professors have different perceptions about academic dishonesty in the Accounting Sciences post graduation strictu sensu program in three categories: fraud and cheating; help to other students in the academic dishonesty practice; and auto-plagiarism and research similarities. Concerning these punishments, differences were found in the five reported categories. It was verified that the professors consider themselves stricter to the students in the academic dishonesty evaluation and that there is a gap in the professors’ evaluation in relation to the students’ ones, since the professor expects that the students have a lower evaluation from the ones they had. The study shows results adherent to the literature, except in the hypothesis that the students consider themselves less strict in the evaluation of the academic dishonesty than the professors, which was not confirmed by the results possibly due to the post-graduation students’ profile be different from the constant one in the other studies carried out in the under-graduation. Besides, almost all the programs have a regulation or a students’ disciplinary code, but few make references to the academically dishonest behaviors and punishments as instructional ways for the academic community. The results still indicate that the character prone to dishonesty, the pressure to publish, the lack of punishment and the achievement of the best performance are the factors that most motivate the academic dishonesty.